2020
DOI: 10.1007/s40962-020-00524-0
|View full text |Cite|
|
Sign up to set email alerts
|

Improving High-Temperature Performance of High Si-Alloyed Ductile Iron by Altering Additions

Abstract: High alloyed Si ferritic ductile irons can offer potential benefits because they combine high strength, ductility at room temperature, and low oxidation rate at high temperature. However, there is one known drawback and that is these cast irons have limited performance during thermal cycling due to a significant drop of ductility at warm temperatures. This decrease in ductility has been linked to poisoning ferrite grain boundaries by Mg. Therefore, thermodynamic simulations were used to identify altering addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…4 for the micrographs of the cycled samples, while it is less apparent but still present on the isothermal sample. Such a feature could be seen on a micrograph in a study by Lekakh et al [21] (their Fig. 10) but was not commented by these authors.…”
Section: Oxide Scale Constitutionmentioning
confidence: 86%
“…4 for the micrographs of the cycled samples, while it is less apparent but still present on the isothermal sample. Such a feature could be seen on a micrograph in a study by Lekakh et al [21] (their Fig. 10) but was not commented by these authors.…”
Section: Oxide Scale Constitutionmentioning
confidence: 86%
“…A twozone horizontal quartz tube furnace, at ambient pressure, was used for these tests with ?/-1 °C temperature control. A special procedure, 8 for decoupling oxidation and deC by measuring weight gain and changes in C, wt.% were conducted. Specimens and crucibles were weighed before and after experiments to determine a total weight change (DG).…”
Section: Experimental Alloys and Test Methodsmentioning
confidence: 99%
“…Thermodynamic simulations of oxidation were performed with assumptions that the local equilibrium condition could be reached between the gas components, formed oxide phases, and SiMo cast iron at different distances from surface. 8 This method was used to predict the phases that could be formed at low (inner scale layer) and high (outer scale layer) oxygen levels. Therefore, the local equilibrium conditions were simulated (FactSage 7.3 software with FSsteel, FToxid, and FactSPS databases 29 ) by adding oxygen stepwise into the alloy streams from the previous simulation step assuming an irreversible reaction.…”
Section: Simulation and Experimental Procedures Alloy Simulation And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were found on investigating various methods of enhancing the properties of ductile iron, including corrosion and wear resistance, high temperature performance, fatigue strength, and reducing internal porosity. Various works have focused on modifying the microstructure through alloying additions, heat treatment, and controlling casting parameters [5][6][7][8][9].…”
Section: Figmentioning
confidence: 99%